Development of Digitalization Program And Establishment of Creative Economic Centers at The Nagari Assistant of UNP In Bisati Padang Pariaman District West Sumatera - Abna Hidayati; Alwen Bentri; Vevi Sunarti; Efni Cerya (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
The industrial revolution 4.0 and digitalization need to be addressed by all levels of government, including the nagari. Nagari or villages are the lowest centers of development and need to take this condition seriously. Obstacles in the field, the nagari does not yet have a structured program for digitizing and developing creative economy centers. The development of the Bisati Go Digital fostered Nagari program aims to help develop the economic potential of Bisati and develop a digitalization program to accelerate community economic development. Development of the assisted villages in Bisati is carried out using the village assistance method with the stages: 1) equalizing perceptions and socializing the program, 2) developing programs through mentoring village apparatus and community human resources, 3) forming a digitization committee, 4) collecting initial data on the potential of the nagari, 5) development of digitalization programs and the establishment of creative economy centers through focus group discussions. The target of the activity is the Nagari Bisati apparatus and the community of MSME actors as many as 25 people. The results of the activity have formed an equalization of public perceptions about digitalization and development of the nagari creative economy and the formation of a digitization committee and collected initial data on the potential of the nagari creative economy in the field of SMEs and tourism.Keywords: digitalization, creative economy, creative economy center